«Questi capitali bestiami, che tanto mi stanno a cuore». Origine e sviluppo della razza bovina Romagnola nella Tenuta Torre di San Mauro di Romagna (secoli XIX-XX). - Barducci, Luca (OS. Opificio della Storia, 2022)
The Torre Estate, purchased in 1828 by Prince Giovanni Torlonia and remained for over a century a large production centre covering about two thousand hectares in the three municipalities of San Mauro, Savignano and Rimini, was the cradle where what we know today as the Romagnola cattle breed was developed. Over the decades, the various administrations that have succeeded each other at the helm of this vast estate have exploited the dual purpose of this cattle: on the one hand, they were the primary source for the fertilization of the fields and an indispensable work tool, on the other, they guaranteed the production of excellent quality meat at the end of their lives. Developed gradually during the thirty years in which the estate was administered by the Pascoli family, this branch of business underwent an evolution at the turn of the nineteenth and twentieth centuries during the administration of Leopoldo Tosi. Through skilful crossbreeding and rigorous selection plans, Tosi established the fundamental characteristics of the breed and guaranteed the estate’s cattle ample consideration at an international level, especially after the great success reported at the Universal Exhibition in Paris in 1900. Thanks in particular to the rich archival documentation relating to the administration of the estate itself, this study aims to analyze the evolution of the Romagnola cattle breed during the nineteenth and twentieth centuries to clarify the path that led to its current state.